AUTISM AND THE APPLICABILITY OF COGNITIVE-BEHAVIORAL THERAPY: A CASE STUDY - de Fátima de Oliveira Brum Augusto de Souza, Cristina; de Souza Fonseca, Bianca; Barcelos da Silva, Cristiana; Castro Manhães, Fernanda (LINKSCIENCEPLACE, 2026)
According to the latest edition of the Diagnostic and Statistical Manual of Mental Disorders in the 5th edition (DSM-V), for a person to be diagnosed with autism, they must present symptoms in two groups. The first is the deficit in communication and social interaction and the second is the pattern of restricted, repetitive behavior, interests and activities. Considering these two groups of symptoms, Cognitive-Behavioral Therapy (CBT) is used in the therapeutic treatment of a young person with autism. CBT has as its principles to work individuals in their totality, strengthening their emotional and cognitive schemes, seeking to produce functional behaviors to solve problems in daily life. The elaboration of the work plan in the cognitive-behavioral approach will be based on the principles of learning, reinforcement and behavioral modeling. The goal of therapeutic treatment with the autistic youngsters is to maximize their potential in language skills, social skills, problem solving, and self-care, freeing them from self-aggression, self-stimulation and aggression. The technique of psychoeducation aims to teach patients to recognize their problems, which generate their difficulties and reinforce their dysfunctional behaviors. CBT assumes that the patient can become his own therapist, and knowledge about what is being done with him or her and how that subject works is the first step in making this happen. The present work aims to identify the behavior of a young man with autism, pointing to an effective intervention using the cognitive-behavioral approach, scoring the symptoms, the contribution of the therapy with the use of CBT and their impact on the quality of daily life.